2022
DOI: 10.3390/make4010013
|View full text |Cite
|
Sign up to set email alerts
|

Robust Reinforcement Learning: A Review of Foundations and Recent Advances

Abstract: Reinforcement learning (RL) has become a highly successful framework for learning in Markov decision processes (MDP). Due to the adoption of RL in realistic and complex environments, solution robustness becomes an increasingly important aspect of RL deployment. Nevertheless, current RL algorithms struggle with robustness to uncertainty, disturbances, or structural changes in the environment. We survey the literature on robust approaches to reinforcement learning and categorize these methods in four different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 87 publications
0
28
0
Order By: Relevance
“…Robust RL. The robustness definition in the RL context has many interpretations [31], including the robustness against action perturbations [32], reward corruptions [33,34], domain shift [35,36], and dynamics uncertainty [37][38][39][40][41][42][43]. The most related works are investigating the observational robustness of an RL agent under state adversarial attacks [17,19].…”
Section: Related Workmentioning
confidence: 99%
“…Robust RL. The robustness definition in the RL context has many interpretations [31], including the robustness against action perturbations [32], reward corruptions [33,34], domain shift [35,36], and dynamics uncertainty [37][38][39][40][41][42][43]. The most related works are investigating the observational robustness of an RL agent under state adversarial attacks [17,19].…”
Section: Related Workmentioning
confidence: 99%
“…There is a surge of interest in researching effective attacks and defenses in RL. Detailed reviews of both fields can be found in [28,76,121].…”
Section: Overviewmentioning
confidence: 99%
“…It has rich meanings that go beyond its literal sense, and motivates a comprehensive framework that includes multiple principles, requirements, and criteria [3]. Recently, there has been exciting progress in the area of trustworthy RL [2,5,48,107,108,121,129,137,140,145,148,165,171,201], which greatly help to advance our understanding of intrinsic vulnerabilities in RL and potential solutions in particular aspects of trustworthy RL. It is clear that the next leap toward trustworthy RL will require a holistic and fundamental understanding of the challenges of these problems, the weakness, and advantages of existing trustworthy RL approaches, and a paradigm shift of trustworthy RL based on existing work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcement learning was first introduced in the 1950s ( Minsky, 1954 ) with the central idea of allowing an agent to learn in its environment and continuously refine its behavioral strategies through constant interaction with the environment and exploration by trial and error ( Moos et al, 2022 ). With the continuous development of RL, algorithms such as Q-learning ( Watkins and Dayan, 1992 ) and SARSA ( Chen et al, 2008 ) have been proposed.…”
Section: Related Workmentioning
confidence: 99%